Implementation of Integrated Livestock Development as an Effort to Eradicate Poverty in Central Aceh District - Hendra Saputra, Asdi Agustar Endry Martius, Maiyestri (Universitas Andalas, 2018)
The development of the Ketapang Integrated Livestock Area (KPTK) in Linge Sub-district, Central Aceh District is one of the implementation of local poverty alleviation policies initiated by Central Aceh District Government. This study aims to determine the implementation of KPTK development as an effort to alleviate poverty in Central Aceh District. This research used survey method with data collection in the form of field observation, in-depth interview, and focus group discussion. Data were analysed using descriptive qualitative. This study found that KPTK development has become a commitment to poverty alleviation. This is found in the central Aceh district development planning system. However, in the implementation there are several obstacles to its development, namely: (1) no synchronization of activities/ programs among related sectors; (2) from a technical point of view, some physical facilities such as roads, bridges and housing and settlement enclosures have been damaged and cannot be used anymore.